Maqasid Syari'ah and the Renewal of the Tradition in Understanding Fiqh - Umar, Abdullah; Detrial Maulana, Mohd; Hidayat Ediz, M; Fadli, Muhammad; Mauliah, Shabrina; Irawan, Aldi; Apriansyah Pratama, Muhammad (Sekolah Tinggi Agama Islam Solok Nan Indah, 2024)
This article explores the paradigm and historical development of maqashid sharia and its relevance in addressing contemporary challenges. As a fundamental objective of Islamic law, maqashid sharia serves as a guiding framework in interpreting and evolving an adaptive fiqh tradition. This study employs a qualitative approach using literature analysis, drawing from classical texts, works of modern scholars, and relevant academic publications. The findings suggest that the concept of maqashid sharia has evolved from a theoretical foundation into a dynamic framework that contributes to contextual and applicable Islamic legal solutions. In the contemporary era, maqashid sharia appears to play a significant role in shaping fiqh renewal, particularly in responding to social, cultural, and technological developments. This study provides insights into how fiqh can be developed to remain responsive to global challenges while upholding the core values of Islamic law.